Conditions of the green transformation. The case of the European Union - Cheba, Katarzyna; Bąk, Iwona; Pietrzak, Michał Bernard (Technological and Economic Development of Economy, 2023)
The main purpose of the paper is to identify the factors that determine the course of green transformation and to assess the current stage and possible directions of change in subsequent years in EU countries. The literature lacks comprehensive studies that show the impact of diverse types of factors on the course of green transformation. For this purpose, two perspectives of the research – economic and environmental – are usually taken into account. This paper also proposes to take social factors into account. The empirical verification was conducted using green growth indicators that are published by the OECD that were compared with factors identified from the literature review. Taxonomic (synthetic) measure of development applying the Weber median and correlation coefficient were used for searching for relationships between the identified groups of indicators described both the changes in the dimension of green growth (internal factors of green transformation) and changes in the dimension of contextual indicators (so-called external factors). The proposed way of combining the results obtained from these two methods of data analysis is also new to research in this field. Its aim is an in-depth exploration of the issue, which enables a 2-step verification of the results obtained. First published online 24 November 2022